GREEN SYNTHESIS, CHARACTERIZATION, AND IN VITRO ANTIMICROBIAL EFFICACY OF SILVER NANOPARTICLES SYNTHESIZED FROM TECTONA GRANDIS WOOD FLOUR - Dangi, Pinki; Op, Jangir (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Silver nanoparticles (AgNPs) are widely used as an antimicrobial agent. Due to the toxicity concerns related to the synthesis of the AgNPs, there is an urgent need of the novel green techniques to synthesis the AgNPs. In the light of the above, we had synthesized the AgNPs with the help of the Tectona grandis commonly known as teak wood. Methods: The aqueous wood floor extract of the T. grandis was used as a reducing agent in the synthesis of the AgNPs. The NPs were synthesized and characterized using different techniques such as ultraviolet-visible spectroscopy, Dynamic light scattering (DLS), Transmission electron microscopy (TEM), and Scanning electron microscopy (SEM). The synthesized NPs were then evaluated for their antimicrobial efficacy against the Gram-negative and Gram-positive bacteria and antifungal activity. Further, in vitro antioxidant efficacy of the AgNPs was calculated using 2,2’-azino-bis(3- ethylbenzothiazoline-6-sulphonic) acid and 2,2-diphenyl-1-picrylhydrazyl assay. Results: From the above analyses, the formation of spherical NPs with an average size of 100 nm was confirmed. Minimum inhibitory concentration (MIC) and minimal biocidal concentration (MBC) of the AgNPs were calculated, MIC and MBC values ranged from 0.50 to 1.8 Î¼g/mL and 0.91 to 3.6 Î¼g/mL, respectively. Conclusion: The prepared NPs were found to be uniform in size with smooth topography. The antibacterial and antifungal efficacy of the NPs was found to be effective on the broad spectrum of microbes. The antioxidant activity of AgNPs was comparable to ascorbic acid.